Application of biochar and alkalis for recovery of sour anaerobic digesters - Natthiporn Aramrueang (2022)
Commercial digesters handling complex waste and organic overloading often encounter unbalanced conditions or failures. With limited studies on the digester recovery from an industry-based waste stream, a complex and high-strength digestate containing up to 79 g COD l−1 from acidified commercial digester was investigated for biochar and alkaline treatments. The addition of biochar and calcium hydroxide successfully decomposed excessive volatile fatty acid up to 18.9 ± 2.5 g l−1 and resumed methane production. The maximum methane yield was obtained from the digester amended with biochar (373.4 ± 6.0 ml g COD−1), followed by calcium hydroxide (350.1 ± 2.5 ml g COD−1). Calcium hydroxide treatment showed a shorter lag phase than the biochar by 44%. Methane production could not be recovered by using sodium hydroxide or untreated digester. This study provides a strategic approach to justify the use of alkalis for restoring sour digesters from industry-based waste streams.